Housing And The Discursive Construction Of Community - Cooper, Matthew; Rodman, Margaret (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1994)
In response to perceived housing problems, many housing cooperatives have been organized in Canada in the last 20 years. These co-ops are resident managed, nonprofit and nonequity. One of their chief goals is the creation of community. A discourse of cooperation frames co-op discussions on contentious issues, e.g. selection of new members, allocation of space, granting of subsidies to low-income members, and member participation. Yet the demands of economic viability, legal and administrative regulation, and the need for capable, active members force co-ops to make difficult practical decisions. This paper investigates how such issues help shape emerging local discourses of community identity.